Waterfall-Based Web Application for Merah Putih Cooperative Registration in Gowa - Sunu Jatmika; Moh. Zainuddin; Rachmat Rachmat (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The cooperative establishment registration process at the Gowa Regency Office of Cooperatives and Micro, Small, and Medium Enterprises (MSMEs) is still predominantly carried out through manual procedures, which often causes long service times, fragmented document storage, administrative duplication, and difficulties in monitoring the status of cooperative establishment applications. This study aims to develop a web-based application for the registration of Merah Putih Cooperatives in Gowa Regency by integrating applicant submission, document uploading, officer verification, and registration data management within a single digital service platform. The research employed the System Development Life Cycle (SDLC) using the Waterfall model, consisting of requirements analysis, system design, implementation, and functional testing. Data needs and system requirements were identified through observation and interviews with relevant officers and prospective cooperative applicants. The application was implemented using PHP, HTML, CSS, JavaScript, and MySQL to support multiuser access, role-based authority, centralized data storage, and structured administrative workflows. The resulting system consists of three main modules: online registration for applicants, verification for administrators, and cooperative registration records management. Functional testing showed that the login process, registration form completion, document upload, application submission, verification status update, and data retrieval functions operated according to the specified requirements. The findings indicate that the developed application can provide a more organized, traceable, and documented mechanism for cooperative establishment registration. However, this study was limited to initial development and functional conformity testing. Future research should evaluate system usability, security, service quality, user satisfaction, and the quantitative effect of the application on administrative processing time.